Prinsip Misi Rasul Paulus Dalam 1 Korintus 9:19-23 Dan Relevansinya Bagi Misi Kontemporer - Purba, Amsal Hasangapon (Hymnos: Jurnal Teologi dan Keagamaan Kristen, 2025)
Contemporary church mission faces complex challenges due to rapid social, cultural, and technological changes, including digital media dominance, globalization, secularism, and increasing pluralism. Most studies on Paul's mission have not deeply connected his flexibility principles with specific challenges faced by contemporary churches in the digital era. This research aims to examine the missionary principles of the Apostle Paul based on 1 Corinthians 9:19-23 and demonstrate their application in contemporary mission contexts. A qualitative method with literature study approach was used to analyze biblical texts and their relevance to contemporary contexts through various credible literary sources. The research findings show that Paul applied two main principles in his mission: the principle of sacrifice, where he voluntarily relinquished his rights and freedom to become a "servant to all people"; and the principle of openness, evident in his ability to "become all thing...